Exploration of Philosophy in Traditional Silat Kumango West Sumatra - Febby Syafita Putri; Ardi Nusri; Albadi Sinulingga; Nurhayati Simatupang (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
The point of this examination is to figure out the philosophy contained in the customary Kumango silat in West Sumatra region. The examining procedure utilized purposive testing method or with specific contemplations so there were 7 sources utilized in this examination. Information assortment methods in this examination utilized perception procedures, documentation studies and meetings with old Kumango Conventional Silat educators. The information obtained will be depicted in subjective expressive structure so an itemized and thorough picture can be obtained. The consequences of the exploration uncover that in Kumango Customary Silat there are numerous methods of reasoning, one of which is the colloquialism "Alam Takambang Jadi Guru" and that implies whatever is a sign in nature, when we learn silat we perceive how battles among tigers and tigers or other brutal creatures result. what should be visible can be utilized as an aide and concentrated in Minangkabau customs. Apart from that, there is also a philosophy in traditional Kumango silat that is applied by the martial artists, namely "Basiang Sabalun Tumbuah, Malantai Sabalun Luluih" applying the principle of introspection or caution.